Radiolucent Lesions Associated with Stainless Steel Mini-Implants During Routine Examination with Cone Beam Computed Tomography-An Observational Study - Felicita, A. Sumathi (2025)
The aim of this study was to determine the prevalence of radiolucent lesions around mini-implants used for orthodontic anchorage due routine evaluation with cone beam computed tomography. Twenty two mini-implants were examined prior to and after orthodontic treatment in young adults requiring absolute anchorage. All mini-implants were placed in the maxillary arch between the second premolar and first permanent molar. CBCT taken immediately after mini-implant placement (T1) and towards the end of treatment (T2) were checked for the presence of radiolucency around the mini-implants. A radiolucent lesion was recorded when it was present in any one of the planes, either the tangential or cross-sectional view of the panoramic window or the coronal or sagittal view of the multiplanar window. The presence/absence of radiolucency was checked individually at T1 and T2 and also compared between T1 and T2. Descriptive statistics with frequency distribution and percentage was done.  31.82% of mini-implants showed a small radiolucency at its tip at T1 and T2. 13.64% of mini-implants showed a linear radiolucency along the length of the mini-implant at T1 and T2. Two mini-implants had periapical lesion at the time of mini-implant at T1 which exaggerated and increased in size at T2 while two mini-implants had a tiny periapical lesion at T1 which resolved at T2. Three mini-implants had radiolucent lesions around the tip of the mini-implant at T1 which changed to a linear radiolucency along the length of the mini-implant at T2 and vice versa.  45.45% of all the mini-implants evaluated showed the presence of radiolucency around it at T1 and 50% of all the mini-implants evaluated showed radiolucency at T2.